2011
DOI: 10.1007/s00401-011-0815-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the solubility and phosphorylation of α-synuclein over the course of Parkinson’s disease

Abstract: Lewy bodies are made from insoluble, phosphorylated α-synuclein, but the earliest changes that precipitate such pathology still remain conjecture. In this study, we quantify and identify relationships between the levels of the main pathologic form of phosphorylated α-synuclein over the course of Parkinson's disease in regions affected early through to end-stage disease. Brain tissue samples from 33 cases at different disease stages and 13 controls were collected through the Australian Network of Brain Banks. 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
108
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 119 publications
(122 citation statements)
references
References 45 publications
12
108
0
2
Order By: Relevance
“…The authors reported a progressive accumulation of pSyn-immunoreactive species in diseased brains compared to healthy controls, as well as a positive correlation between pSyn levels and the severity of disease symptoms. A similar study using brain samples from PD patients also reported a drastic accumulation of pSyn-positive inclusions in different brain regions at the late stages of the disease [128]. Together, these results suggest that the occurrence of pSyn is linked to the severity of disease progression.…”
Section: α-Syn Phosphorylation At Serine129 and Cellular Eventssupporting
confidence: 56%
“…The authors reported a progressive accumulation of pSyn-immunoreactive species in diseased brains compared to healthy controls, as well as a positive correlation between pSyn levels and the severity of disease symptoms. A similar study using brain samples from PD patients also reported a drastic accumulation of pSyn-positive inclusions in different brain regions at the late stages of the disease [128]. Together, these results suggest that the occurrence of pSyn is linked to the severity of disease progression.…”
Section: α-Syn Phosphorylation At Serine129 and Cellular Eventssupporting
confidence: 56%
“…This is a well-established technique to study aggregated α-syn 17, 18, 20, 21 a protein that is normally soluble in its native form but gain amyloidogenic or increased aggregation properties with disease progression or with genetic mutations. Nonetheless, some groups have used slight variations in SDS concentrations in their buffers (8% or 10% instead of 5%) 21,22,30 . The SDS is an anionic detergent and solubilises α-syn oligomers that can include membrane bound forms of α-syn, whereas urea, a chaotropic reagent denatures the insoluble aggregated and fibrillar or amyloidogenic forms of α-syn 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The α-syn monomers were recognized to similar extents by all 4 antibodies although these can have variation depending on whether the α-syn antibody epitope is located either in the N-terminal or Cterminal 29 . Similarly, specific antibodies for phospho-alpha synuclein determine distinct high-molecular weight α-synuclein species 20,21 . In the protocol described here, the highly characterized antibody Syn-1 has been used [19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations